Two new combinations and a new synonym in the genus Odontarrhena (Brassicaceae) - Španiel, Stanislav (Phytotaxa, 2019)
In the recent treatment of the tribe Alysseae (Španiel et al. 2015), many taxa of the genus Alyssum Linnaeus (1753: 650) were transferred to Odontarrhena C.A.Mey. ex Ledebour (1830: 15). Odontarrhena clearly differs from Alyssum in molecular markers and morphological characters such as a predominantly compound inflorescence and monospermous locules of silicles (versus a usually simple raceme and silicles with two seeds in each locule). A list of accepted species and numerous new combinations of Odontarrhena were recently published (Španiel et al. 2015). However, two species names, Alyssum mozaffarianii Kavousi (2001: 48) and A. baldaccii Vierhapper ex Nyárády (1928: 123), were previously overlooked or misinterpreted and their respective combinations within Odontarrhena were not established. The new combinations are presented here together with taxonomic notes, a new synonym and newly designated lectotypes of four names of Odontarrhena taxa.